Optimizing culture conditions for establishment of hairy root culture of semecarpus anacardium L. - Panda, Bhuban Mohan; Mehta, Urmil J.; Hazra, Sulekha (3 Biotech, 2017)
Semecarpus anacardium L. is a tree species which produces secondary metabolites of medicinal importance. Roots of the plant have been traditionally used in folk medicines. Different strains of Agrobacterium rhizogenes (A4, ATCC15834 and LBA 9402) were used for induction of hairy roots in in vitro grown tissues of the plant. Hairy root initiation was observed after 25-30 days of infection. Optimum transformation frequency of 61% was achieved on leaf explants with ATCC15834 strain. Infection time of 30 min resulted in greater transformation frequency compared to 10 and 20 min, respectively. The hairy roots cultured in growth regulator-free semi-solid woody plant medium differentiated into callus. Whole shoots infected with ATCC 15834 were found to produce more transformants upon co-cultivation for 4 (65%) and 5 (67%) days. Induction of hairy roots in stem explants infected with ATCC 15834 was lower (52%) compared to leaves (62%) after 4 days of co-cultivation. In A4 and LBA9402 strains transformation efficiency was 49 +/- 2.8% and 36 +/- 5.7% in shoots after 4 days of co-cultivation. Transformation frequency was higher in ATCC15834 strain, irrespective of explants. The hairy roots of S. anacardium elongated slowly upon transfer to half-strength liquid medium. After 3-4 passages in liquid medium slender hairy roots started differentiating which were separated from the original explants. Visible growth of the roots was observed in hormone-free liquid medium after 2-3 months of culturing. Polymerase chain reaction with gene-specific primers from rol A, B and C genes confirms the positive transformation events.
Keywords: Hairy root culture; In vitro culture; rol genes; Semecarpus anacardium; Transformation